2010
DOI: 10.4103/0974-7796.62915
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility pattern in urinary isolates of gram negative bacilli with special reference to AmpC β-lactamase in a tertiary care hospital

Abstract: Introduction:Resistance to higher antimicrobial agent is commonly seen in gram negative bacilli. This issue is a challenging problem to the medical practitioners in addition to it is financial impact on the health care system.Objectives:To document the prevalence of multi drug resistant gram negative bacilli isolated from urine of patients attending the Urology Department of Tertiary care Hospital of western India in year 2008.Results:Out of total 328 isolates, 118 (35.98%) E.coli, 72 (21.95 %) Klebsiella, 64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 5 publications
(5 reference statements)
0
13
0
Order By: Relevance
“…Study conducted by Wazait HD et al, in 2001 reported 0.90% and by Patel MH et al, in 2010 reported 34% resistant to ceftazidime. 18,19 This shows that resistance among pseudomonas species has increased more over last 10 years. Highest resistance was found to aminoglycosides (tobramycin) 92.30%.…”
Section: Discussionmentioning
confidence: 95%
“…Study conducted by Wazait HD et al, in 2001 reported 0.90% and by Patel MH et al, in 2010 reported 34% resistant to ceftazidime. 18,19 This shows that resistance among pseudomonas species has increased more over last 10 years. Highest resistance was found to aminoglycosides (tobramycin) 92.30%.…”
Section: Discussionmentioning
confidence: 95%
“…In present study pseudomonas was found 69.23% resistant to both ceftazidime and cefaperazone. 18,19 This shows that resistance among pseudomonas species has increased more over last 10 years. Highest resistance was found to aminoglycosides (tobramycin) 92.30%.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly out of 14 urine specimens, cefepime was effective in 8 (57.1%) isolates. In a study done by Patel et al, out of total 64 urinary isolates of Pseudomonas aeruginosa, resistance rate of cefepime was 15.6% [14].…”
Section: Discussionmentioning
confidence: 97%